Perception about the Mental Health of a multidisciplinary team in an emergency during the COVID pandemic 19 (Research, Society and Development, 2021)
Objective: To report the experience about the perception of the mental health of a multiprofessional health team during the COVID-19 pandemic. Methodology: Descriptive research was carried out on the perception of professionals from a multiprofessional health team working on the front lines during the COVID-19 pandemic, in an Emergency Department located in a city in the state of Rio de Janeiro. Results and discussion: During the experience, the demand for mental and psychological health was perceived, in addition to the physical exhaustion of the unit's professionals, as well as the team's interest in having support from mental health professionals to face the COVID-19 pandemic. Final considerations: COVID-19 will continue to be a constant for the scientific community as well as for the professionals of health care teams for the next few years. Its genetic changes, and its capacity to have changed everyone's life, makes it research material and it is of general interest that new knowledge about this disease and its consequences be shared, so that we are always ahead in preventions, care and treatments, physical and mental.